500 nm induced tunable syngas synthesis from CO2 photoreduction by controlling heterojunction concentration. Issue 40 (24th April 2020) - Qiu, Conghui; Hao, Xiaojie; Tan, Ling; Wang, Xian; Cao, Wenjing; Liu, Junyan; Zhao, Yufei; Song, Yu-Fei
Abstract : CO2 photoreduction to tunable syngas on a CoAl-LDH/MoS2 heterostructure with different catalyst concentrations under irradiation above 400 nm. Abstract : A heterostructured CoAl-layered double hydroxide/MoS2 nanocomposite photocatalyst (CoAl-LDH/MoS2 ) for CO2 photoreduction was prepared by simple electrostatic interactions. The syngas ratio (H2  : CO) was precisely tuned from 1.3 : 1 to 15 : 1 by altering only the catalyst concentration in the photocatalytic CO2 reduction system under visible light ( λ > 400 nm). Interestingly, a rather high evolution rate can be obtained from CO2 photoreduction to CO up to 4575 μmol g −1 h −1 even under irradiation above 500 nm.